O pessoal do Cais Bar: trajetória de formação do habitus musical de uma gração de artistas e intelectuais das décadas de 1980 e 1990 - Santos, Fábio Costa (2023)
This dissertation has as its theme: “The People of Cais Bar: Trajectory of Formation of the Musical Habitus of a Generation of Artists and Intellectuals from the 1980s and 1990s”. The object of study is the process of formation of a generation of artists and intellectuals who were part of the 1995 double LP, entitled: Pessoal do Cais Bar – Novos Compositores e Intérpretes cearenses. The approach is qualitative, and data collection occurred through semi-structured interviews. Through the analysis of data provided by the agents, we investigated their training trajectories, since their origin, establishing the contribution of the family environment to the incorporation of a primary habitus, as well as uncovering how the contribution of the school context occurred, through school festivals. of music and presentations in schools. We realized that the majority of agents did not have experience in formal musical education environments, building their knowledge through interactions between peers. These relationships provided them with advantages, and these enabled their insertion in the musical scenes in which they wanted to orbit. We can also understand the influence of informal environments (bars) on the agents' musical training, as they functioned as a kind of music school. It should be noted that the majority of agents used these types of tools, because through the activities and musical interactions that took place in these places, they accumulated knowledge, which was important for the development of their careers. We also elucidate the processes that consecrated and consolidated the trajectories of these agents in the field in which they circulated, relating the relevance of the agents' participation in the recording of the Pessoal do Cais Bar LP, as a preponderant factor in terms of visibility and inclusion of a new generation of Ceará musicians in the music market. In conclusion, this study revealed the trajectories of the agents, characterizing where they came from, how they became what they are and how each one made their way in the music scene.